Edukasi Keluarga Berencana Kenali Dan Pahami KB IUD Di Dusun II Desa Sukasari Kec. Air Periukan Kab. Seluma - Ramadani, Egy Novenda; Febyana, Febyana; Irmanda, Julianike; Putri, Yesi (Utami Publisher, 2025)
The lack of public knowledge about contraceptive methods, particularly the Intrauterine Device (IUD), has resulted in the suboptimal use of this long-term contraceptive method. Health education counseling on IUD-based family planning aims to improve the community’s understanding—especially among women of reproductive age—of the benefits, how it works, as well as the advantages and disadvantages of the IUD as a family planning method.The activity was carried out in the form of counseling using leaflets and presentations to the residents of Sukasari Village, Air Periukan Subdistrict, Seluma Regency. The results showed enthusiasm and active participation from the community during the question-and-answer and discussion sessions. This educational initiative is expected to raise awareness about choosing the right contraceptive method according to individual needs and to encourage appropriate use of long-term contraception.